Jakarta: A Secular City (A Study of Neosecularization of the Middle Class Muslim Community in Metropolitan Jakarta) - Yusuf, Choirul Fuad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
Originally, this paper is a summative work of the writer’s research conducted in 2013-2014, entitled “Neo-sekularisasi: Studi Sekularisasi pada Komunitas  Muslim  Kelas  Menengah  Metropolitan  Jakarta”  (Neo-secularization:  A Study  of  Secularization  at  the  Middle  Class  Muslim  Community  in Metropolitan Jakarta). This study tries to portray of how the role of Islam as a  religion  has  been  treated  or  internalized  by  its  followers, particularly amongst  the  middle  class  Muslim  in  Jakarta  as  the  metropolitan. In  other word, the writer wants to explicate of how the middle class Muslim Jakarta internalized  and  implemented  their  religious  teachings  adhered.  Using  the mixed  methodology,  the  study  highlights  a  numerous  conclusions  of  the findings. First, at the institutional dimension, secularization appeared in the form  of  religious  decline  of  the  religious  institution,  decline  of  religious leaders,  and  religious  transformation.  Second,  at  the  normative  dimension, secularization  manifested  in  the  type  of  desacralisation,  disengagement  of religion.  While  at  the  cognitive  dimension,  secularization  has  been  being crystallized  as  religious  segmentation  and  secularism.  But,  above  all,  the type,  process,  and  trend  of the  secularization  occurred amongst  the  middle class  of  Muslim  community  is  different  for  the  secularization  experienced commonly in the West.